Musculoskeletal anomalies in children with Down syndrome: an observational study. Issue 5 (16th May 2019) - Foley, Charlene; Killeen, Orla G
Abstract : Background: Musculoskeletal complications of Down syndrome (DS) are common but infrequently reported. The combination of ligamentous laxity and low muscle tone contributes to increased risk of a number of musculoskeletal disorders and a delay in acquisition of motor milestones. The primary aim of this study was to describe musculoskeletal anomalies reported in a national cohort of children with DS. Methods: This was an observational study. Children with DS, aged 0–21 years, were invited to attend a musculoskeletal assessment clinic conducted by a paediatric physician. Relevant musculoskeletal history and clinical findings were documented. Results: Over an 18-month period, 503 children with DS were examined (56% male). The median age was 8.1 years (0.6–19.2). Pes planus was almost universal, occurring in 91% of the cohort. A range of other musculoskeletal anomalies were observed, with inflammatory arthritis (7%) and scoliosis (4.8%) occurring most frequently after pes planus. Delay in ambulation was common; the median age to walk was 28 months (12–84). Conclusion: Children with DS are at increased risk of a number of potentially debilitating musculoskeletal problems. These conditions can present in variable manners or be completely asymptomatic. Pes planus is common; therefore, early consideration of orthotics and lifelong appropriate supportive footwear should be considered. Delayed ambulation is frequently noted. A significant proportion of children with DS have arthritis; however, despite a high prevalence, it is often missed, leading to delayed diagnosis. An annual musculoskeletal assessment for all children with DS could potentially enable early detection of problems, allowing for timely multidisciplinary team intervention and better clinical outcomes.